The Influence of Accounting Learning, Fintech Knowledge and Fintech Efficiency on the Interest in Using Gopay for Accounting Study Program Students at UNP Kediri - Irawati, Rika Jepri; Widiawati, Hestin Sri; Faisol, Faisol (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research Objective: The purpose of this research is to ascertain whether accounting program students at Nusantara PGRI Kediri University will be interested in using Gopay if they have knowledge of financial accounting, fintech knowledge, and ease of use. Research Method: The SPSS version 21 application is used for data processing, and the following research uses a quantitative approach. The population in this research is students of the accounting study program at Nusantara PGRI Kediri University who are familiar with the Gopay digital application. This research uses non-probability sampling as its sampling strategy. 121 people were sampled for this study. The data in the following research were analyzed using multiple linear regression. Research Finding: This research analysis reveals that the interest of accounting program students at Nusantara PGRI Kediri University in using Gopay is positively and significantly influenced by financial accounting knowledge, fintech knowledge, and ease of use.